Catch it if you can: is the catch phase overlooked in weightlifting? - Valenzuela, B.; Kipp, K. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to present a new method of dividing the phases of weightlifting exercises and describe the accompanying barbell biomechanics. Ten competitive female weightlifters performed 4 sets at intensities ranging from 85 to 100% of their previous one repetition maximum (1RM) in snatch and clean. A motion capture system was used to record 3-D barbell trajectories for all attempts. Barbell kinematic and kinetic data were compared between the pull, turnover, and catch phases of the snatch and clean. During the catch phase, the average force exerted on the bar was greater than during the other two phases for both lifts even though it was applied over a shorter distance in comparison (p<0.05). The demands of the catch phase should be taken into account in future studies when analyzing the technical requirements of these exercises.